Where can a person be ”Home” arrested? - Stanciu, Mihai-Alexandru (Technium Social Sciences Journal, 2021)
The provisions of criminal proceedings do not clearly define what is meant by ”domicile” when they provide for the possibility of a defendant being arrested at home during criminal proceedings. The lack of such a definition can have major practical implications, especially when the defendant is not the owner of the building where his arrest is ordered, and his owner does not agree with the measure, which can pose the problem of being restricted by a state action, the property right of the person, as his fundamental and constitutional right.